The Application of Shape Language in Komodo Character Design for the IP FANI “Indonesian Children's Fable” - Rita Kemalasari; Nuria Indah Kurnia Dewi; Cora Emilia Malikiyano (Journal of Animation and Games Studies, 2026)
This research aims to create a character design strongly infused with Nusantara local icons, which will become part of the FANI (Fabel Anak Indonesia/Indonesian Children's Fable) IP, given the significant audience demand for educational content among early childhood. Based on these criteria, one of the Nusantara endemic animals, the Komodo dragon, was selected to be part of the FANI IP and is realized as two twin Komodo children characters, "Koko and Momo". The Komodo character design utilizes shape language to bring out the characters' personalities, which are humorous and helpful, thereby making a positive impression on early-age children. The creation method employs the stages of creative thinking as outlined in Wallas's theory. The results show that the application of shape language in creating character designs of the Nusantara endemic animal, the Komodo dragon, successfully produces cute and friendly character designs appropriate for the target audience, early childhood, especially through educational content as an effort to conserve biodiversity in Indonesia for future generations.